Academic Leadership in Fostering Safety Culture in Maritime Educational Institutions - Muhammad Sahid (Universitas Negeri Yogyakarta, 2026)
Safety is a crucial aspect in the maritime sector due to the high level of risk associated with operational activities in this field. Therefore, maritime educational institutions play a strategic role in instilling safety awareness and behavior among cadets before they enter the workforce in the maritime sector. This study aims to analyze the role of academic leadership in fostering a safety culture within maritime educational institutions. This research employs a quantitative approach with a survey design. Data collection was conducted by distributing questionnaires to fifth-semester cadets majoring in Nautical and Marine Engineering. The total number of respondents in this study was 41. Data analysis was performed using validity tests, reliability tests, and simple linear regression analysis via statistical software. The results indicate that academic leadership has a positive and significant influence on safety culture within maritime educational institutions. The coefficient of determination (R²) indicates that academic leadership accounts for 41.6% of the variation in safety culture, while the remainder is influenced by other factors outside the scope of this study. These findings suggest that academic leadership plays a crucial role in strengthening safety culture through academic policies, the learning process, and practical activities within the maritime education environment.